Analisis Resepsi Remaja Bekasi Selatan terhadap Toksik Maskulinitas dalam Film Seri Euphoria - Perdita Safitri, Tishara; Delliana, Santi (UNIVERSITAS KALBIS, 2025)
Toxic masculinity refers to male behavioral patterns that promote dominance, emotional repression, and aggression, often to the detriment of themselves and others. This study investigates how young women in South Bekasi interpret toxic masculinity as represented in the television series Euphoria. Using Stuart Hall’s Encoding-Decoding theory as the analytical framework, the study employs a qualitative research approach through in-depth interviews with five informants aged 23–26. The research adopts a constructivist paradigm to understand how individual and social contexts shape audience reception. Findings reveal that all participants align with the dominant-hegemonic position, interpreting toxic masculinity by the filmmaker’s constructed message. This study highlights the significant influence of media representations on audience perceptions of gender norms. Furthermore, it contributes to the broader discourse on how mass media perpetuates or challenges traditional gender expectations among youth, particularly in an Indonesian sociocultural context.